Analisis Ketahanan Gempa Rumah Tembokan Beton Bertulang di Perumahan Graha Arradea - Yoresta, Fengky Satria (Department of Civil Engineering, Diponegoro University, 2018)
The concept of earthquake resistant houses is basically that all building components must be well tied each other. In addition, quality of materials and workmanship must also be good so as to produce a strong building when receiving shocks. This study aims to determine whether houses in Perumahan Graha Arradea (Tahap 3 in Ciherang Village, Dramaga Subdistrict, Bogor District - West Java are built following the design principles of earthquake resistant houses. The research is conducted by observing the construction process at the location. Every stage of the construction process is recorded using a digital camera (Sony Cyber-shot DSC-W730). Interviews are also conducted on related parties to obtain accurate informations. The results conclude that the houses that are built have not met minimum requirements for design of earthquake resistant masonry houses with reinforced concrete frame. In addition to quality of some materials that have not met minimum requirements, the quality of workmanship of building component is also still low. The ties of all building components have not been properly connected.